Observation de la convection profonde en mer d'Irminger sur la période 2002-2015 par les flotteurs Argo. - Piron, Anne (Université de Bretagne Occidentale, 2015)
The deep convection events are important because they form the intermediate and deep water masses feeding the global circulation. The Labrador Sea is the main site of deep convection in the North Atlantic Ocean and produces the intermediate Labrador Sea Water (LSW). The Irminger Sea was also cited but was forgotten during decades because of the lack of direct observations. This thesis provides the first description of the Irminger Sea deep convection at basin scale, thanks to the Argo data. Three convective events occurred in the Irminger Sea since 2010. During the 2011-2012 winter, the convection reached 1000 m and is explained by the sequence of the Greenland tip jets. The event of the 2013-2014 winter, reaching 1300 m, is characterized by a strong preconditionning and a weak forcings by the Greenland tip jets. The convection event of the 2014-2015 winter, reaching 1700 m, shows many of persistant tip jets. The advection of LSW from the Labrador Sea explains the deepest mixed layers observed during the last two winters. The results show that deep convection in the Irminger Sea is not a rare isolated event and plays a significant role on the climate balance. Les évènements de convection profonde sont importants car ils forment les masses d’eau intermédiaires et profondes qui nourrissent la circulation globale. La mer du Labrador, qui forme la Labrador Sea Water (LSW), est le site le plus documenté de l’océan Atlantique Nord. La mer d’Irminger a également été citée mais n’est pas entièrement reconnue à cause du manque d’observations directes. Cette thèse fournit la première description de la convection profonde en mer d’Irminger à l’échelle du bassin grâce aux données Argo. Trois évènements de convection se sont produits en mer d’Irminger depuis 2010. Au cours de l’hiver 2011-2012, la convection atteint 1000 m et est expliquée par la séquence d’apparition des tip jets groenlandais. La convection de l’hiver 2013-2014, qui atteint 1300 m, est caractérisée par un préconditionnement particulièrement important et ...